Computer-Aided Analyses and Optimisation of Fluid-Thermal Systems using Excel - (:unkn) unknown (Self publishing, 2025)
The three thermofluid subjects (thermodynamics, fluid mechanics, and heat-transfer), which are fundamental components of the curricula for most engineering specialisations, are traditionally taught by using data tables for fluid properties and charts for approximate analytical solutions of complex systems and design-based analyses. Although the repetitive use of tables and charts helps the students to acquire the three lower-order thinking skills (LOTS); Remember, Understand, and Apply, of tables and charts are not suitable for conducting sensitivity and design optimisation type of analyses that help them to acquire the higher-order thing skills (HOTS); Analyse, Evaluate, and Create. In this respect, computer-aided learning (CAL) methods can be more effective as shown by research conducted at a number of top-class universities. CAL methods are also more suitable than traditional methods for online teaching that has now become a necessity rather than a choice. Realising the benefits of CAL, most thermofluid textbooks now include computer-based exercises and mini-projects. Although a number of commercial software are available and can be used for such exercises and projects, these might not be available or affordable to many students and academic institutions particularly in developing countries. General-purpose spreadsheet applications, such as Microsoft Excel, can be the ideal solution to this problem. With its wide availability on personal computers, ease of use, and powerful graphical tools, Excel has been used as a computational platform in various engineering courses. Numerous papers on the use of Excel as a teaching aid have also been published in relevant journals or presented at specialised conferences over the past two decades. However, most of the previous experiences and efforts, if not all, focus on a particular type of analyses or a particular feature of Excel and do not describe a general pedagogical approach. Moreover, the papers, which are written in the form of short research articles, cannot provide sufficient information for using Excel as an effective educational modelling platform for the various types and levels of thermofluid analyses. This book is the first volume in a set of books that complement the previous efforts by describing an Excel-based modelling platform which is adequate for computer-aided thermofluid analyses and showing how the platform can be used for conducting the various types of these analyses. The book adopts a learning-by-example approach and many of its examples have been adopted from standard thermofluid textbooks so that the students can verify their Excel solutions and look for any additional information if required.
Computer-Aided Analyses and Optimisation of Fluid-Thermal System
These are chapters from an unpublished book